Bioactive properties of the aromatic molecules of spearmint (Mentha spicata L.) essential oil: a review. Issue 6 (25th February 2022) - Zhang, Lu-Lu; Chen, Yan; Li, Zhi-Jian; Li, Xiao; Fan, Gang
Abstract : Spearmint aromatic molecules have a variety of bioactivities, including antimicrobial, antioxidant, insecticidal, anticonvulsant, antinociceptive, and transcutaneous penetration enhancing activities and multi-pharmacological effects. Abstract : Spearmint belongs to the genus Mentha in the family Labiatae (Lamiaceae), which is cultivated worldwide for its remarkable aroma and commercial value. The aromatic molecules of spearmint essential oil, including carvone, carveol, dihydrocarvone, dihydrocarveol and dihydrocarvyl acetate, have been widely used in the flavors and fragrances industry. Besides their traditional use, these aromatic molecules have attracted great interest in other application fields ( e.g., medicine, agriculture, food, and beverages) especially due to their antimicrobial, antioxidant, insecticidal, antitumor, anti-inflammatory and antidiabetic activities. This review presents the sources, properties, synthesis and application of spearmint aromatic molecules. Furthermore, this review focuses on the biological properties so far described for these compounds, their therapeutic effect on some diseases, and future directions of research. This review will, therefore, contribute to the rational and economic exploration of spearmint aromatic molecules as natural and safe alternative therapeutics.